Cognitive Flexibility in Early Childhood: A Contemporary View of the Development of Flexible Goal-Oriented Behavior - Yeşim Yavaşlar Doğru; Daniel Carroll; Emma Blakey (Psikoloji Çalışmaları)
Cognitive flexibility is usually described as a skill that allows us to revise our behaviors or ideas as the task objective or the environment changes. Over 20 years, in addition to inhibitory control and working memory, cognitive flexibility has been presented as one of the main executive functions and has been considered to develop at around three to four years of age when children learn to easily switch from sorting cards according to one rule (e.g., shape) to the other rule (e.g., colour). This classic view of cognitive flexibility has been highly influential in improving our knowledge about the development of cognitive flexibility. However, in recent years, the way cognitive flexibility is understood has changed remarkably that leads the way that it should be thought and studied has also changed. The present paper aims to present a contemporary view of cognitive flexibility by reviewing recent advances in methodological and analytical techniques used to study cognitive flexibility. Particularly, recent research has started to use less constrained rule-switching tasks to assess cognitive flexibility and use more advanced modelling-based statistical approaches to analyse cognitive flexibility. These recent advances suggest that cognitive flexibility is not a stand-alone skill that emerges during the preschool years. Instead, cognitive flexibility is the culmination of the development of controlled, goal-oriented behavior that happens across a broader age span and in a much more diverse range of contexts than previously thought. While the earlier developments in cognitive flexibility in the first two years of life are underpinned by attention and language, the later developments in cognitive flexibility from around three years onwards are underpinned by inhibitory control and working memory.